The Effect of Pulsed Magnetic Field on The Healing of Infected Cutaneous Wounds at Thigh Region in Rabbits: Ibrahim MH Alrashid ,Ashwaq R Nazal, Hana K Ibrahim - Alrashid, Ibrahim MH . (The Iraqi Journal of Veterinary Medicine, 2011)
Magnetic therapy was applied in the present study, which play two roles; as antimicrobial (Escherichia coli, Staphylococcus auras, Streptococcus spp, Klebsialla ,and Pseudomona ) and as stimulator to tissue repair.24 rabbits were used in this study, they divided into two groups; 1st group(treated group) contains 20 rabbits, 2nd group (control group) contains 4 rabbits, the last subdivided into two subgroup (standard control subgroup and sham-control subgroup, the left side of all animals in control group is standard control subgroup, while the left side is sham-control subgroup). After surgery to all, the wounds were exposed to pulsed magnetic field except standard control subgroup, they healed with conventional treatment, 1st group(treated group) and sham-control subgroup were treated with(600 Gauss,50 Hz) twice daily for 30 minutes during 7 days. Microbiologically, the bacterial Petri dish were exposed to pulsed magnetic field in present study (600 Gauss, 50Hz) 30 minutes/day for one only, after re-culture of these bacteria at new media, there weren’t bacteria growth appeared which were used in present study. Clinically, the clinical signs of wounds were recorded at 1, 3, 5,7, and 9 days post induce wound ; the sham-control subgroup was healed after 5.5 days after induce wound, 1st treated group was healed after 7-10 day post induce wound, while standard control subgroup was healed after 9 day post induce wound. Biopsies were toke after 3,5,7,and 9 days post induce wound, the histopathological study of sham-control subgroup revealed that show more develop compare with other.